Rapid cortical responses to the unpleasantness of natural surfaces and their relationship to image statistics - Ogawa, Narumi; Motoyoshi, Isamu (Vision research (Oxford), 2025)
Humans not only perceive material properties of natural surfaces but also evaluate their affective qualities, such as pleasantness or unpleasantness. Recent psychophysical studies suggest that such emotional impressions can arise directly from low-level image statistics, independent of object recognition. To elucidate the neural mechanisms underlying these immediate affective responses, we recorded visual evoked potentials (VEPs) while participants viewed 150 images of natural surfaces varying in affective valence. We identified occipital VEP components emerging around 100–150 ms after stimulus onset that were significantly correlated with subjective unpleasantness ratings. Moreover, these unpleasantness-related VEPs were accurately predicted by a linear combination of VEP components associated with a small set of diagnostic image statistics. Our findings indicate that early visual cortical activity encodes image features that give rise to unpleasant affective responses, supporting the notion that rapid, low-level visual processing can directly contribute to the emotional evaluation of visual textures and materials.